Bell-trap effectiveness to capture Crypturellus obsoletus and Crypturellus tataupa (Aves: Tinamidae) in southern Brazil - Luiz Liberato Costa Corrêa; Darliane Evangelho Silva; Phamela Katharina Müller; Maria Virginia Petry (Acta Scientiarum. Biological Sciences, 2023)
Specific techniques for the efficient capture of forest tinamous in a short sampling time are yet poorly described in the literature. Here, we report the efficiency of the bell-trap in the capture of Brown Tinamou (Crypturellus obsoletus) and Tataupa Tinamou (Crypturellus tataupa), in southern Brazil. We used three bell-traps adapted with casting nets. In 80 hours of sampling effort, four adult individuals of C. obsoletus were captured, in a forest area in the Pampa Biome. This study area is located in the municipality of São Sepé, state of Rio Grande do Sul, Brazil. Subsequently, in 16 hours of sampling effort in a forest area of the Atlantic Forest domain, one individual of C. obsoletus and one of C. tataupa were captured. This other study area is located in the municipality of Passo do Sobrado, RS. The bell-trap method has already been reported as efficient in capturing Yellow-legged Tinamous (Crypturellus noctivagus), in southern Brazil. However, since forest tinamous are cryptical birds, field adaptations are often necessary to achieve success in sampling activities. The use of this method proved efficient in the capture of forest tinamous, generating an important tool for the collection of bioecological data of this group of birds, which still represents a lack of studies.